2012
DOI: 10.1128/jb.00528-12
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Individual σ B -Dependent General Stress Genes to Oxidative Stress Resistance of Bacillus subtilis

Abstract: The general stress regulon of Bacillus subtilis comprises approximately 200 genes and is under the control of the alternative sigma factor B . The activation of B occurs in response to multiple physical stress stimuli as well as energy starvation conditions. The expression of the general stress proteins provides growing and stationary nonsporulating vegetative cells with nonspecific and broad stress resistance. A previous comprehensive phenotype screening analysis of 94 general stress gene mutants in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…In contrast to alkA, B. subtilis aag does not seem to be under the control of the Ada response (43); however, aag expression is regulated in concert with the general stress B regulon (25,26). Furthermore, inducible levels of expression of this gene were detected during spore germination/outgrowth (44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to alkA, B. subtilis aag does not seem to be under the control of the Ada response (43); however, aag expression is regulated in concert with the general stress B regulon (25,26). Furthermore, inducible levels of expression of this gene were detected during spore germination/outgrowth (44).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, we postulate that aag is an additional member of the G regulon. Of note, katX was also reported to be part of the B regulon (25,26), and previous work also demonstrated that F directs katX expression inside the forespore compartment during B. subtilis sporulation (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In B. subtilis, katA is mainly expressed in growing cells, and its transcription can be stimulated by hydrogen peroxide (40). On the other hand, katB transcription takes place during the transition growth phase as part of the B regulon; of note, in addition to heat, ethanol, and hyperosmotic stresses, the expression of this regulon can also be stimulated by oxidative-stress inducers, including hydrogen peroxide (41,59). On the basis of these observations, we can speculate that Cr(VI) promotes oxidative stress in vegetative B. subtilis cells and that such an event activates the PerR and B transcriptional responses to counteract the deleterious effects of the oxyanion.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies showed that different severe stresses elicited a common secondary oxidative stress. Severe stresses, including heat and acid stress treatments, caused radical formation in B. cereus (24)(25)(26), and a phenotypic screening of B. subtilis mutants showed that many of the genes displaying multiple severe stress management effects appeared to be involved in protection against oxidative damage (16,27). Also, in B. weihenstephanensis, a secondary oxidative stress response may be a common component of multiple severe stress stimuli, and it is conceivable that pretreatment with mild oxidative stress provides bacterial cells with a better ability to survive these conditions.…”
Section: Figmentioning
confidence: 99%